IDENTIFIKASI STRATEGI PEMASARAN MARKETING MIX 7P PADA SEKTOR UMKM - Zailani, Rinawati; Suprihatiningsih, Suprihatiningsih (Unitri Press, 2024)
This research aims to analyze the implementation of the 7P marketing mix strategy for small and medium enterprises